Governance Arrangements That Fit Social‐Ecological Context Are Associated With Fishery Sustainability - Mateja Nenadović; Alfredo Giron; Timothy Frawley; Adrian Munguia‐Vega; Kara E. Pellowe; Erica Ferrer; David Gill; Blanca González‐Mon; Andrew F. Johnson; Emilie Lindkvist; Fiorenza Micheli; Amy H. Weaver; et al. (Fish and Fisheries, 2026)
In many parts of the world, natural resources are primarily managed by governance arrangements at the local level. Those arrangements range from collective, such as cooperatives and associations, to individualistic, such as patrons and owner‐operators. A key question is how such arrangements influence resource use and associated social and ecological outcomes. We hypothesize that sustainable resource use is not associated with a specific governance arrangement, but instead that every type of arrangement has a certain set of social and ecological conditions under which sustainable resource use is feasible. This hypothesis was empirically investigated using fisheries landings data from Mexico. We found that sustainable resource use can be achieved through multiple governance arrangements provided that they are matched to appropriate social‐ecological contexts. Our findings help identify which governance arrangements are best suited to particular contexts and provide the initial building blocks for developing a theory of governance contextual fit in social‐ecological fishing systems.

Putting Regional Fisheries Management Organisations' Climate Change House in Order - Kamal Azmi; Graham Pilling; Johann Bell; Yi‐Jay Chang; Adele Dutilloy; Timothy H. Frawley; Paul Hamer; John Hampton; Quentin Hanich; Tyla Hill‐Moana; Jhen Hsu; Glenn Hurry; et al. (Fish and Fisheries, 2025)
Climate change is expected to have significant impacts on the biology, abundance and distribution of transboundary fish stocks, not only among neighbouring countries within the jurisdictions of regional fisheries management organisations (RFMOs) but also between adjacent RFMOs. Using South Pacific albacore tuna ( Thunnus alalunga ) as a case study, we highlight how RFMOs need to understand the impacts of climate change on transboundary stocks under their purview with greater certainty. We identify four areas of research that should assist RFMOs to adapt their scientific processes—strengthened understanding of changes in the biology of target stocks; enhanced collection of data to support modelling; improved modelling of catch‐per‐unit of effort (CPUE) to better reflect climate change impacts on stock abundance for assessments; and ensuring that scientific advice is adaptive and robust to climate change, including through implementation of tested harvest strategies. Investments in these research areas should enable RFMOs to improve the science underpinning management measures designed to sustain transboundary stocks and increase fishery performance during climate change.

Socio-economic impacts and responses of the fishing industry and fishery managers to changes in small pelagic fish distribution and abundance - Felipe J. Quezada-Escalona; Desiree Tommasi; Isaac C. Kaplan; Pierre-Yves Hernvann; Timothy H. Frawley; Dorleta Garcia; Leire Ibaibarriaga; Sonia Sánchez-Maroño; Carryn de Moor; Jennifer Beckensteiner; Amy M. Schueller; Diana Feijó; et al. (Reviews in Fish Biology and Fisheries, 2025)
Small Pelagic Fish (SPF) exhibit large fluctuations in abundance and distribution in response to environmental variability. To maintain the resilience of fishing communities and develop effective and equitable climate adaptation strategies, improved understanding of how the fishing industry responds to spatio-temporal shifts within and across SPF populations is of critical importance. In this paper, we examine the responses of the fishing industry and resource managers to shifts in SPF availability worldwide and identify the resulting socioeconomic impacts. Leveraging SPF case studies from around the globe, we synthesize and compare the social-ecological linkages and feedbacks mediating how SPF fisheries respond to changes in marine ecosystem structure and function associated with (1) spatial shifts in species distribution and habitat availability, (2) ‘boom and bust’ population dynamics, or (3) changes in fish size and quality. Our case studies illustrate multiple paths towards the resilience of small pelagic fisheries and the fishing industry dependent upon them while emphasizing the need for increased coordination and cooperation across sectors and scales as climate change progresses. Drawing from the lessons offered by historical responses, as environmental variability increases, efforts to increase the flexibility and dynamism of SPF harvest portfolios and management strategies, licensing regimes, and international catch and allocation agreements may be required to ensure resource sustainability and human well-being.

Self-governance mediates small-scale fishing strategies, vulnerability and adaptive response - Timothy H. Frawley; Blanca González-Mon; Mateja Nenadovic; Fiona Gladstone; Keiko Nomura; José Alberto Zepeda-Domínguez; Salvador Rodriguez-Van Dyck; Erica M. Ferrer; Jorge Torre; Fiorenza Micheli; Heather M. Leslie; Xavier Basurto (Global Environmental Change, 2024)

Dynamic human, oceanographic, and ecological factors mediate transboundary fishery overlap across the Pacific high seas - Timothy H. Frawley; Barbara Muhling; Stephanie Brodie; Hannah Blondin; Heather Welch; Martin C. Arostegui; Steven J. Bograd; Camrin D. Braun; Megan A. Cimino; Nima Farchadi; Elliott L. Hazen; Desiree Tommasi; et al. (Fish and Fisheries, 2024)
The management and conservation of tuna and other transboundary marine species have to date been limited by an incomplete understanding of the oceanographic, ecological and socioeconomic factors mediating fishery overlap and interactions, and how these factors vary across expansive, open ocean habitats. Despite advances in fisheries monitoring and biologging technology, few attempts have been made to conduct integrated ecological analyses at basin scales relevant to pelagic fisheries and the highly migratory species they target. Here, we use vessel tracking data, archival tags, observer records, and machine learning to examine inter‐ and intra‐annual variability in fisheries overlap (2013–2020) of five pelagic longline fishing fleets with North Pacific albacore tuna ( Thunnus alalunga , Scombridae). Although progressive declines in catch and biomass have been observed over the past several decades, the North Pacific albacore is one of the only Pacific tuna stocks primarily targeted by pelagic longlines not currently listed as overfished or experiencing overfishing. We find that fishery overlap varies significantly across time and space as mediated by (1) differences in habitat preferences between juvenile and adult albacore; (2) variation of oceanographic features known to aggregate pelagic biomass; and (3) the different spatial niches targeted by shallow‐set and deep‐set longline fishing gear. These findings may have significant implications for stock assessment in this and other transboundary fishery systems, particularly the reliance on fishery‐dependent data to index abundance. Indeed, we argue that additional consideration of how overlap, catchability, and size selectivity parameters vary over time and space may be required to ensure the development of robust, equitable, and climate‐resilient harvest control rules.

Projecting climate change impacts from physics to fisheries: A view from three California Current fisheries - James A. Smith; Mercedes Pozo Buil; Barbara Muhling; Desiree Tommasi; Stephanie Brodie; Timothy H. Frawley; Jerome Fiechter; Stefan Koenigstein; Amber Himes-Cornell; Michael A. Alexander; Steven J. Bograd; Nathalí Cordero Quirós; et al. (Progress in Oceanography, 2023)

Social relationship dynamics mediate climate impacts on income inequality: evidence from the Mexican Humboldt squid fishery - Laura G. Elsler; Timothy Haight Frawley; Gregory L. Britten; Larry B. Crowder; Timothy C. DuBois; Sonja Radosavljevic; William F. Gilly; Anne-Sophie Crépin; Maja Schlüter (Regional Environmental Change, 2021)
Small-scale fisheries are critically important for livelihoods around the world, particularly in tropical regions. However, climate variability and anthropogenic climate change may seriously impact small-scale fisheries by altering the abundance and distribution of target species. Social relationships between fishery users, such as fish traders, can determine how each individual responds and is affected by changes in fisheries. These informal cooperative and competitive relationships provide access, support, and incentives for fishing and affect the distribution of benefits. Yet, individuals’ actions and impacts on individuals are often the primary focus of the economic analyses informing small-scale fisheries’ formal management. This focus dismisses relevant social relationships. We argue that this leads to a disconnect between reality and its model representation used in formal management, which may reduce formal fisheries management’s efficiency and efficacy and potentially trigger adverse consequences. Here, we examine this argument by comparing the predictions of a simple bioeconomic fishery model with those of a social-ecological model that incorporates the dynamics of cooperative relationships between fish traders. We illustrate model outcomes using an empirical case study in the Mexican Humboldt squid fishery. We find that (1) the social-ecological model with relationship dynamics substantially improves accuracy in predicting observed fishery variables to the simple bioeconomic model. (2) Income inequality outcomes are associated with changes in cooperative trade relationships. When environmental temperature is included in the model as a driver of species production dynamics, we find that climate-driven temperature variability drives a decline in catch that, in turn, reduce fishers’ income. We observe an offset of this loss in income by including cooperative relationships between fish traders (oligopoly) in the model. These relationships break down following species distribution changes and result in an increase in prices fishers receive. Finally, (3) our social-ecological model simulations show that the current fishery development program, which seeks to increase fishers’ income through an increase in domestic market demand, is supported by predictions from the simple bioeconomic model, may increase income inequality between fishers and traders. Our findings highlight the real and urgent need to re-think fisheries management models in the context of small-scale fisheries and climate change worldwide to encompass social relationship dynamics.

Changes to the structure and function of an albacore fishery reveal shifting social‐ecological realities for Pacific Northwest fishermen - Timothy H. Frawley; Barbara A. Muhling; Stephanie Brodie; Mary C. Fisher; Desiree Tommasi; Gwendal Le Fol; Elliott L. Hazen; Stephen S. Stohs; Elena M. Finkbeiner; Michael G. Jacox (Fish and Fisheries, 2021)
Marine fisheries around the globe are increasingly exposed to external drivers of social and ecological change. Though diversification and flexibility have historically helped marine resource users negotiate risk and adversity, much of modern fisheries management treats fishermen as specialists using specific gear types to target specific species. Here, we describe the evolution of harvest portfolios amongst Pacific Northwest fishermen over 35+ years with explicit attention to changes in the structure and function of the albacore ( Thunnus alalunga, Scombridae) troll and pole‐and‐line fishery. Our analysis indicates that recent social–ecological changes have had heterogenous impacts upon the livelihood strategies favoured by different segments of regional fishing fleets. As ecological change and regulatory reform have restricted access to a number of fisheries, many of the regional small ( 60 ft) targeting albacore are more specialized now than previously observed, even as participation in multiple fisheries has become increasingly common for this size class. In describing divergent trajectories associated with the albacore fishery, one of the US West Coast's last open‐access fisheries, we highlight the diverse strategies and mechanisms utilized to sustain fisheries livelihoods in the modern era while arguing that alternative approaches to management and licensing may be required to maintain the viability of small‐scale fishing operations worldwide moving forward.

How adaptive capacity shapes the Adapt, React, Cope response to climate impacts: insights from small-scale fisheries - Kristen M. Green; Jennifer C. Selgrath; Timothy H. Frawley; William K. Oestreich; Elizabeth J. Mansfield; Jose Urteaga; Shannon S. Swanson; Francisca N. Santana; Stephanie J. Green; Josheena Naggea; Larry B. Crowder (Climatic Change, 2021)

Heterogeneous Perceptions of Social-Ecological Change Among Small-Scale Fishermen in the Central Gulf of California: Implications for Adaptive Response - Timothy H. Frawley; Larry B. Crowder; Kenneth Broad (Frontiers in Marine Science, 2019)

Reconstructing overfishing: Moving beyond Malthus for effective and equitable solutions - Elena M Finkbeiner; Nathan J Bennett; Timothy H Frawley; Julia G Mason; Dana K Briscoe; Cassandra M Brooks; Crystal A Ng; Rosana Ourens; Katherine Seto; Shannon Switzer Swanson; Jose Urteaga; Larry B Crowder (Fish and Fisheries, 2017)
Inaccurate or incomplete diagnosis of the root causes of overfishing can lead to misguided and ineffective fisheries policies and programmes. The “Malthusian overfishing narrative” suggests that overfishing is driven by too many fishers chasing too few fish and that fishing effort grows proportionately to human population growth, requiring policy interventions that reduce fisher access, the number of fishers, or the human population. By neglecting other drivers of overfishing that may be more directly related to fishing pressure and provide more tangible policy levers for achieving fisheries sustainability, Malthusian overfishing relegates blame to regions of the world with high population growth rates, while consumers, corporations and political systems responsible for these other mediating drivers remain unexamined. While social–ecological systems literature has provided alternatives to the Malthusian paradigm, its focus on institutions and organized social units often fails to address fundamental issues of power and politics that have inhibited the design and implementation of effective fisheries policy. Here, we apply a political ecology lens to unpack Malthusian overfishing and, relying upon insights derived from the social sciences, reconstruct the narrative incorporating four exemplar mediating drivers: technology and innovation, resource demand and distribution, marginalization and equity, and governance and management. We argue that a more nuanced understanding of such factors will lead to effective and equitable fisheries policies and programmes, by identifying a suite of policy levers designed to address the root causes of overfishing in diverse contexts.